UPAYA MENINGKATKAN KEMAMPUAN MENGHAFAL ASMAUL HUSNA PADA ANAK USIA DINI MELALUI METODE BERNYANYI DI TK NUSANTARA - Juwarsih, Juwarsih (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
This study aims to improve the ability of early childhood students to memorize Asmaul Husna through the implementation of the singing method at TK Nusantara, Sonomartani Village, Kualuh Hulu District. The type of research used is Classroom Action Research (CAR) conducted in two cycles, each consisting of four stages: planning, action implementation, observation, and reflection. The subjects of this study were 10 children from group B at TK Nusantara. Data were collected through observation, interviews, and documentation, then analyzed descriptively and qualitatively to determine the improvement in children’s ability to memorize Asmaul Husna. The results showed that the use of the singing method significantly improved the children’s ability to memorize Asmaul Husna. In the first cycle, the average mastery level reached 48.75%, while in the second cycle it increased to 78.75%. This improvement indicates that through singing, children found it easier to remember, pronounce correctly according to makhraj, tajwid, and fashohah, and were able to memorize without the teacher’s assistance. Therefore, the singing method is proven to be an effective and enjoyable approach to enhancing memorization skills of Asmaul Husna while fostering children’s love for Islamic values from an early age.